Arduino-based Automatic Light Design Using a Light-dependent Resistor Sensor at dr. H.A Rotinsulu Hospital - Saputra, Rizal; Rizki, Ardelia Astriany (Politeknik Piksi Ganesha Indonesia, 2024)
Lights are one of the fundamental needs in the standard of living; if the light is cleared out, it'll squander power, and this often happens since you disregard to turn it off. in the list to fast improvement within the field of innovation the sum of power demand tends to extend quickly. This increment in demand can be caused by the expanding number of individuals utilizing electrical technology.In this case, a robotization light plan was made utilizing an Arduino-uno-based light sensor that can be set to turn on and off naturally, agreeing to the escalation of daylight so that it'll suit the desires of the lamp.The controller utilized is the Arduino microcontroller. The program connected to the microcontroller serves to initialize and design the equipment and examines the flag input from the light sensor, which at that point forms it is by being given a few conditions to create yield. In this case, a robotization light plan was made utilizing an Arduino-uno-based light-based Sensor that can be turned on and off, consequently concurring with the concentrated daylight received to suit the desires of the light.